PENYELARASAN ANTARA PERMINTAAN DENGAN PENYEDIAAN GURU PRODUKTIF BERDASARKAN SPEKTRUM KEAHLIAN DI SMK DALAM PERSPEKTIF DESENTRALISASI PENDIDIKAN - A.G Tamrin (Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2013)
Structuring expertise with the rising spectrum of competence and skill development of the ratio between the SMA: SMK is 30 SMA : 70 SMK has consequences on the fulfillment of teachers in vocational productive. Teachers' needs for productive subjects did in fact still not be met by LPTK and become increasingly difficult to meet due to teachers earning the required majority has not been organized by LPTK. The need for truly productive teachers perceived as an obstacle difficult to solve in the area. For that, the necessary alignment between demand with the supply of teachers by utilizing the model teacher's certification activities and cooperation between LPTK with Non LPTK with Local Government done with synergize the availability of customize and can be generated LPTK teacher and scholar who produced non LPTK but the field of knowledge in accordance with the requirements SMK.